Health Insurance Deepening and Its Impact on Maternal Healthcare Demand in Private Hospitals in Kenya - George N. Mose; Joseph Abuga Orayo (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Promotion of maternal healthcare services through the expansion of health insurance coverage has been a core strategy that has been adopted in the reduction of maternal and child mortalities in Kenya. In this study, we seek to establish how health insurance coverage and benefits influence the demand for maternal health utilization in private hospitals in Kenya. The study utilized the latest Kenya Demographic Household Survey 2014 data to estimate the relationship. The binary probit regression model was employed in estimation. From the findings, only 15 percent of mothers were enrolled in a health insurance plan, whereas 14 percent of the women reported to have attended antenatal clinics in private health facilities, and 13 percent benefited from skilled delivery in private healthcare facilities. Results further revealed that health insurance ownership led to a significant increase in the likelihood of utilizing maternal health care services in private hospitals in Kenya. Similarly, age of the mother, marital status, birth order, higher education level, all wealth index categories, and employment status were cofactors associated significantly with use of healthcare services. It was concluded that the advent and increase of health insurance coverage is associated with a significant rise in demand of maternal healthcare services in private hospitals. This study argues that the current health subsidies would be more effective if they were channeled through health insurance with wider coverage of private hospitals. The study recommends reforms in policies and guidelines governing insurance coverage, which we argue would significantly bring down the cost of insurance coverage, thus become more accessible to more Kenyans.